Results of biological control of chestnut blight in Slovakia - Juhásová, Gabriela; Adamcíková, Katarína; Robin, Cécile (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2005)
The health condition of Castanea sativa in the Stiavnicko-krupinská region of Slovakia was evaluated and the incidence of the fungus Cryphonectria parasitica was noted. A total of 2274 trees were examined. The degree of injury was expressed on a scale varying from zero to five and an index of health condition, IHC, was calculated from these data. The values of IHC varied from 0.12 to 1.36. From 1992 to 1997, we treated 714 cankers using hypovirulent strains of C. parasitica obtained from INRA Clermont-Ferrand. Callusing was observed on 32.7% of the treated cankers.